The Halal Lifestyle of Academic Communities in the Islamic Religious Colleges in Kediri in Strengthening the Halal Industry - Muhamad Wildan Fawaid; Novia Saka, Dijan; Subandono, Agus; Fasa Ilham Haq, Muhammad; Waeno, Mahammadaree (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2024)
Halal refers to the laws outlined by Allah in the Quran for permissible actions and practices based on Sharia principles.  As a Muslim-majority country, Indonesia aspires to be a global leader in the implementation of the Halal lifestyle, with higher education institutions acting as change agents. This research combined quantitative and qualitative methods. The results of the analysis revealed that all dependent variables have a significant relationship simultaneously with the independent variable, namely Lifestyle. There are two types of effects on lifestyle: positive and negative. Reference Group, Family, Personality, Perception, Motives, and Demographics are the factors that show a positive effect. Culture and Experience, on the other hand, have a negative effect. Overall, the academic community at Kediri's Islamic Religious College is very supportive of the halal industry.